Effects of pain neuroscience education combined with neuromuscular exercises on pain, functional disability and psychological factors in chronic low back pain: A study protocol for a single-blind randomized controlled trial. - Ehsan Alvani; Bahram Sheikhi; Amir Letafatkar; Giacomo Rossettini (PLoS ONE)
Objective Chronic low back pain (CLBP) is a prevalent health condition worldwide. Several therapeutic interventions aim to improve CLBP. Pain Neuroscience Education (PNE) helps patients better understand their pain from biological and physiological perspectives, which clinicians use to reduce pain and disability in patients with chronic musculoskeletal conditions. Neuromuscular exercises (NMS) are also treatments adopted in CLBP. This study will investigate whether PNE combined with an NMS program improves pain, functional and psychological outcomes more than NMS alone in patients with CLBP. Methods In this single-blind randomized controlled trial, 60 patients (male and female; age range, 30-60 years) diagnosed with CLBP will be randomly assigned to one of the following groups: (1) PNE plus NMS (n = 30; 24 sessions of PNE plus NMS in a total of 8 weeks, 3 each week), and (2) NMS alone (n = 30; 24 sessions of NMS sessions in a total of 8 weeks, 3 each week). Outcome assessors will be blinded to the group allocation. The primary outcome will be pain. Secondary outcomes will be disability, fear-avoidance beliefs about work and physical activity, self-efficacy, exercise anxiety, and kinesiophobia. Outcomes will be assessed at baseline, after 8 weeks of intervention, and 6 months post-intervention. Discussion The findings of this RCT will help shed light on new treatment strategies to address the biopsychosocial dimensions of CLBP. The study protocol will be conducted in a clinical setting, offering the opportunity for future implementation in healthcare systems. Moreover, it will help clarify whether a combined treatment (PNE with NMS) is more effective than NMS alone for improving pain, functional and psychological outcomes in CLBP. Trial registration Study registration: The study was prospectively registered in the Iranian Registry of Clinical Trials-IRCT20190427043384N2 (https://www.irct.ir/trial/69146). Registered on March 17, 2023.